The Wife as Politician and Her Role in Realizing the Sakinah Family - Nina Chairina; Ahmad Hidayat; Nurul Ma’rifah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The role of a wife in maintaining the dignity of a Sakinah family at home is a problem faced when women have a career in politics. This condition is also a polemic for experts in interpretation and jurisprudence about women's careers in the public sphere. This study aims to find a comprehensive perspective on how wives as politicians play their role in creating a Sakinah family, based on Islamic law and phenomenological studies. The study was conducted using the Systematic Literature Review (SLR) method. The results of the study indicate that in creating a sakinah family, there are principles that must be used as a basis by wives as politicians, including 1) making faith and piety the foundation for family and career, 2) respecting each other's rights and responsibilities, 3) maintaining harmony in communication, 4) sharing roles and responsibilities, 5) protecting oneself from slander, and 6) consulting with husbands/family members in decision making.